Análisis del derecho y derechos humanos - Rey Navas, Fabio Iván (Corporación Universitaria Americana, 2022)
The vision of analysis is complemented with the understanding of human rights from a methodological vision based on the critical school as a form of emancipation of the being, which is concretized for example in the discrimination towards women as a way to increase their protection, and is complemented from the comparative vision of human rights and fundamental rights in European and American courts.